Design and Development of an Unmanned Surface Vehicle - Dr. Suchendra K R; P Samuel Standly; Praveen Kumar D V; Thanuj M S; Chethan Kumar P (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
The project addresses the urgent challenge of plastic pollution in confined water bodies through the development of a specialized Unmanned Surface Vehicle (USV) for efficient debris collection. Employing a catamaran-inspired design featuring PVC hulls and a modular debris collection system, the USV combines buoyancy with effective debris capture capabilities. Integrated with DC motors and an ESP32 microcontroller, the USV offers both remote- controlled and autonomous operation modes. In remote control mode, users navigate the USV via Bluetooth using the Dabble app, while in autonomous mode, onboard cameras and Python- based computer vision algorithms enable real-time debris detection and navigation. This versatile solution, adaptable to various environmental conditions, promises significant advancements in debris collection efficiency and environmental conservation efforts, heralding a new era in sustainable water management practices.
Keywords: Unmanned Surface Vehicle; Debris Collection; Remote Control; Autonomous Operation; Catamaran Design